Evaluation of Vessel Sealing Performance Among Ultrasonic Devices in a Porcine Model. (August 2015) - Tanaka, Ryota; Gitelis, Matthew; Meiselman, Danny; Abar, Bijan; Zapf, Matthew; Carbray, JoAnn; Vigneswaran, Yalini; Zhao, Jin-Cheng; Ujiki, Michael
Background . As new technologies emerge, it is imperative to define which new devices are most likely to provide a reproducible, effective result for the patient and surgeon. The purpose of our study was to analyze 3 commercially available ultrasonic energy devices; the Sonicision (SC), the Harmonic ACE (HA), and the THUNDERBEAT (TB). Material and Methods . Eight female Yorkshire pigs were used for data collection and vessel harvest. Three devices were evaluated and compared with each other with respect to seal failure and cutting speed in vivo. After vessel harvest, one end of the fragment was sent for histological evaluation, and the other was used for burst pressure measurement testing in a blinded fashion. The coagulation and cut levels of all the generators were set up at a similar and constant level. Results . Eighty-four vessels (47 arteries and 37 veins) were tested. Mean vessel diameter was equal among the groups. Cutting speed was significantly faster with TB (3.4 ± 0.7 seconds) than SC or HA (5.8 ± 2.4 and 6.1 ± 3.1 seconds; P < .0001). Burst pressure trended higher after ligation with TB (505.4 ± 349.4 mm Hg) than SC and HA (435.8 ± 403.0 and 437.6 ± 291.3 mm Hg). There were 2 seal failures in the SC group and HA group and none in the TB group. Histologically, the perpendicular width of tissue seal with TB (1.250 ± 0.55 mm) was significantly longer than that of the SC and the HA (0.772 ± 0.23 and 0.686 ± 0.23 mm; P < .0001). Conclusions . TB has proven to provide the most rapid and reliable seal. Therefore, TB may be safer and may decrease time during surgical procedures.